GAMBARAN PENGETAHUAN DAN PARITAS IBU YANG MEMBERIKAN ASI EKSKLUSIF DI WILAYAH PUSKESMAS CAHAYA NEGERI KABUPATEN SELUMA TAHUN 2017 - Rahmawati, Diyah Tepi; Taliah, Taliah; Nelazyani, Lucky; Eka, Afreliya (Journal Of Midwifery, 2018)
The decline in the rate of exclusive breastfeeding is one of the factors causing death in infants. Breast-fed infants are 17 times more likely to have pneumonia, and are 3-4 times more likely to get respiratory infection than infants exclusively breastfed (Maryunami, 2012).This study aimed to determine the description of knowledge and parity of mothers providing exclusive ation at Cahaya Negeri health center of Seluma regency in 2017.The type of research is descriptive quantitative with the entire population of Mothers having infants aged 6-12 months at Cahaya Negri health center area as many as 193 babies. This research was conducted on June 18 to July 25, 2017 with the Accidental Sampling by 66 respondents. This research used a descriptive analysis.The results obtained from 24 mothers who gave exclusive breastfeeding, (54.2%) were knowledgeable enough and (54.2%) mothers were with multiparity parity. Of the 42 mothers who did not breastfeed Exclusively (52.4%) had less knowledge and most (59.5%) of the mothers were with primiparity parityTo Cahaya Negeri Seluma Health Center of Seluma regency is expected to cooperate with health institute to do giving information to the community, especially pregnant women and mothers who have a toddler.